Influence of enteral nutrition support via nasointestinal tube combined with fast-truck surgery on nutritional status, complications and postoperative rehabilitation of patients with severe head injury (经鼻肠管营养支持联合快速康复外科理念对重症颅脑损伤患者营养状况、并发症及术后恢复的影响) - LU Huixin (卢卉欣) (中西医结合护理)
Objective To investigate the influence of enteral nutrition support via nasointestinal tube combined with fast-truck surgery on nutritional status, complications and postoperative rehabilitation of patients with severe head injury. Methods Totally 100 patients with severe head injury were divided into the control group (n=58) and the observation group(n=42) according to the nutrition support methods. All patients received nursing interventions based on the theory of fast-truck surgery. Patients in the control group received enteral nutrition by nasogastric tube, and those in the observation group were given enteral nutrition by nasointestinal tube. The nutritional status［serum total protein (TP), prealbumin (PAB)、hemoglobin (Hb)］, intestinal mucosal barrier function ［intestinal fatty acid-binding protein (I-FABP), plasma D- lactic acid (D-LA)］, inflammatory factor ［interleukin-6 (IL-6), hypersensitive C-reactive protein (hs-CRP), tumor necrosis factor-α(TNF-α), postoperative complication, postoperative rehabilitation［Fugl-meyer Motor Function Rating Scale (FMA), The Mini-Mental State Examination (MMSE), Glasgow Outcome Scale (GOS)］ of patients were measured and compared between two groups. Results Patients in the observation group had higher levels of TP, PAB, Hb and lower levels of Ⅰ-FABP, D-LA, IL-6, hs-CRP, TNF-α compared with those in the control group after treatment(P＜0. 05). The incidence of complications in the observation group was lower than that in the control group(19. 05% vs. 37. 93%, P＜0. 05). Scores of FMA and MMSE in the observation group were higher than those in the control group(P＜0. 05). A better outcome of GOS in the observation group was reported compared with that in the control group (P＜0. 05). Conclusion The enteral nutrition support via nasointestinal tube combined with fast-truck surgery is potentially effective to improve the nutritional status and intestinal mucosal barrier function, reduce the inflammatory response and postoperative complications, improve the postoperative rehabilitation and quality of life among patients with severe head injury. (目的 探究经鼻肠管肠内营养支持联合快速康复外科理念(FTS)对重症颅脑损伤患者营养状况、并发症及术后恢复的影响。方法 回顾性分析2019年6月—12月医院收治的100例SHI患者的临床资料, 按治疗方式的不同分为对照组(n=58)和观察组(n=42)。两组均采取基于FTS的干预措施, 其中对照组行常规经鼻胃管肠内营养支持, 观察组行经鼻肠管肠内营养支持。比较两组治疗前后营养状况［血清总蛋白(TP)、前白蛋白(PAB)、血红蛋白(Hb)］、肠黏膜屏障功能［血清肠型脂肪酸结合蛋白(Ⅰ-FABP)、血浆D-乳酸(D-LA)］、炎症因子［白细胞介素-6(IL-6)、超敏-C反应蛋白(hs-CRP)、肿瘤坏死因子-α(TNF-α)及并发症、术后恢复［运动功能Fugl-Meyer运动功能评定量表(FMA)、简易精神状态评价量表(MMSE)、格拉斯哥预后量表(GOS)］情况。结果 与对照组相比, 观察组治疗后TP、PAB、Hb水平更高, Ⅰ-FABP、D-LA水平及血清IL-6、hs-CRP、TNF-α水平更低, 差异有统计学意义(P＜0. 05)。观察组并发症总发生率低于对照组(19. 05% vs 37. 93%, P＜0. 05)。观察组治疗后FMA、MMSE评分高于对照组(P＜0. 05), 且观察组治疗后GOS评分等级较对照组更优(P＜0. 05)。结论 经鼻肠管营养支持联合FTS可有效改善SHI患者营养状况、肠黏膜屏障功能, 抑制炎症反应, 进而降低并发症发生率, 提高术后恢复质量。)